Could bacteriophages isolated from the sewage be the solution to methicillin-resistant Staphylococcus aureus? - Tan, Cheng Siang; Nurul Aqilah, Binti Aqiludeen; Tan, Ruixin; Gowbei, Annabel; Mijen, Alexander Beemer; Louis, Santhana Raj; SIti Fairouz, Binti Ibrahim (Malaysian Medical Association, 2020)
Introductions: The emergence of multidrug-resistant bacteria such as Methicillin-Resistant Staphylococcus aureus (MRSA) complicates the treatment of the simplest infection. Although glycopeptides such as vancomycin still proves to be effective in treating MRSA infections, the emergence of vancomycin-resistant strains limits the long term use of this antibiotic. Bacteriophages are ubiquitous bacterial viruses which is capable of infecting and killing bacteria including its antibiotic-resistant strains. Bactericidal bacteriophages use mechanisms that is distinct from antibiotics and is not affected by the antibioticresistant phenotypes. Objectives: The study was undertaken to evaluate the possibility to isolate bacteriolytic bacteriophages against S.aureus from raw sewage water and examine their efficacy as antimicrobial agents in vitro. Methodology: Bacteriophages were isolated from the raw sewage using the agar overlay method. Isolated bacteriophages were plaque purified to obtain homogenous bacteriophage isolates. The host range of the bacteriophages was determined using the spot test assay against the 25 MRSA and 36 MSSA isolates obtained from the Sarawak General Hospital. Staphylococcus saprophyticus, Staphylococcus sciuri and Staphylococcus xylosus were included as non-SA controls. The identity of the bacteriophages was identified via Transmission Electron Microscopy and genomic size analysis. Their stability at different pH and temperature were elucidated. Results: A total of 10 lytic bacteriophages infecting S.aureus were isolated and two of them namely ΦNUSA-1 and ΦNUSA-10 from the family of Myoviridae and Siphoviridae respectively exhibited exceptionally broad host range against >80% of MRSA and MSSA tested. Both bacteriophages were specific to S.aureus and stable at both physiologic pH and temperature. Conclusion: This study demonstrated the abundance of S.aureus specific bacteriophages in raw sewage. Their high virulence against both MSSA and MRSA is an excellent antimicrobial characteristic which can be exploited for bacteriophage therapy against MRSA.